Immediate effects of different types of stretching exercises on badminton jump smash - Jang, H. S.; Kim, D.; Park, J. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: Since different types of stretching exercises may alter athletic performance, we compared the effects of three types of stretching exercises on badminton jump smash. METHODS: Sixteen male collegiate badminton players performed one of three different stretching exercises in a counterbalanced order on different days. Static stretching had seven typical stretches, while dynamic stretching involved nine dynamic movements, and resistance dynamic stretching was performed with weighted vests and dumbbells. Before and after each stretching exercise, subjects performed 20 trials of jump smashes. Dependent measurements were the jump heights during jump smashes, velocities of jump-smashed shuttlecocks, and drop point of jump-smashed shuttlecocks. To test the effects of each stretching exercise, we performed mixed model ANOVAs and calculated between-time effect sizes (ES). RESULTS: Each stretching exercise improved the jump heights during jump smashes (type main effect: F(2,75)=1.19, P=0.31; static stretching: 22.1%, P<0.01, ES=0.98; dynamic stretching: 30.1%, P<0.01, ES=1.49; resistance dynamic stretching: 17.7%, P=0.03, ES=0.98) and velocities of jump-smashed shuttlecocks (type main effect: F(2,75)=2.18, P=0.12; static stretching: 5.7%, P=0.61, ES=0.39; dynamic stretching: 3.4%, P=0.94, ES=0.28; resistance dynamic stretching: 6%, P=0.50, ES=0.66). However, there were no differences among the stretching exercises for any measurement. The drop point of jump-smashed shuttlecocks did not change (interaction: F(2,75)=0.88, P=0.42). CONCLUSIONS: All stretching exercises improved badminton jump smash performance, but we could not determine the best protocol. Since badminton requires high-speed movement and explosive force, we suggest performing dynamic stretching or resistance dynamic stretching.